2019
DOI: 10.3390/ijerph16244922
|View full text |Cite
|
Sign up to set email alerts
|

Using a Mobile Phone App to Identify and Assess Remaining Stocks of In Situ Asbestos in Australian Residential Settings

Abstract: Asbestos-containing materials (ACMs) were used extensively throughout much of the 20th century and can still be found in many Australian homes. Therefore, we developed a mobile application (“app”), called ACM Check, which guides users through a home inspection to identify and assess certain types of in situ ACM. A cross-sectional study was conducted using the app to collect data on the type and condition of in situ asbestos in Australian residential settings. Since being released in June 2017, we have received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Surprisingly, it was found that cement sheeting and waterpipe accounted for 90% of the asbestos consumption in Australia. Another study in the Australian residential buildings also showed high positive detection rates of asbestos backing board to the electrical meter boxes and asbestos eves [2]. Overall, asbestos-containing materials presented in 82.3% of the sampled houses.…”
Section: Methods Replicabilitymentioning
confidence: 84%
See 2 more Smart Citations
“…Surprisingly, it was found that cement sheeting and waterpipe accounted for 90% of the asbestos consumption in Australia. Another study in the Australian residential buildings also showed high positive detection rates of asbestos backing board to the electrical meter boxes and asbestos eves [2]. Overall, asbestos-containing materials presented in 82.3% of the sampled houses.…”
Section: Methods Replicabilitymentioning
confidence: 84%
“…Although a series of bans for the use of hazardous materials in construction have been imposed since the 1970s, an appreciable quantity of contaminated materials remains in the existing building stocks [1]. The frequent presence of asbestos-containing materials [2,3] and PCBs (polychlorinated biphenyls)-containing components [4] is the result of mass production and adoption in the 1920s-1990s [5]. In addition to the negative concerns of human health and the environment, demolished and renovated projects become more expensive and take a longer time if hazardous materials are encountered unexpectedly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-assessment questionnaire results were validated by performing accuracy tests and agreement with expert investigations before analyzing Cohen's kappa statistics [11]. Their findings highlighted the frequent presence of asbestos (82.3 %) in the residential environment [12], not far from the results (95 %) of the study by Franzblau et al [8]. Both the top-down and bottom-up research methods identified prevalent types of ACMs and prioritized remediation in residence.…”
Section: Machine Learning In Hazardous Materials Identificationmentioning
confidence: 97%
“…Several studies have tried to develop innovative and cost-efficient methodologies to overcome the abovementioned problems. The potential of applying statistical operations in registered records [8,9], creating digital tools for field inventory [10][11][12], etc., was explored as alternative ways for supplementing the existing methods. These novel methods successfully characterized the amount and types of ACMs in residential buildings despite the different data input and collection processes.…”
Section: Introductionmentioning
confidence: 99%